English Reading Habit of Students With Different L1 Reading Habit, L2 Reading Proficiency, and Reading Attitude (e-Journal of Linguistics, 2020)
Second language reading is affected by reading habitof first language, the reading proficiency, thestrategies of reading, and reading attitude (Sundari,2013). The questions lies in this study are (1) howdoes English reading habit of students with differentL1 reading habit, L2 reading proficiency, and readingattitude? (2) And what is the factor mostly affectedthe English reading habit? This is a qualitative-quantitative research, this is a qualitative research forits purpose to describe the English habit, and thisstudy is also a quantitative research for its purpose tofind the most factors affected the English readinghabit by applying the formula of correlation to see thehighest coefficient correlation. The instruments ofthis study are two questionnaires of (1) readingattitude by M.N. Gomleksiz (2004) and (2) L2reading habit by Ro Eunseok and Alice (2014) whichare administered to 23 students. The result of thisstudy are: (1) English reading habits of the subjectsfound out various and different due to thecombination of the three factors collaborated, from23 students there are 11 of them are in low Englishreading habit, 8 of them are in moderate Englishreading habit, and 4 of them are in high Englishreading habit. (2) Though, L1 reading habit is mostlylow but L2 reading proficiency is the factor mostlyaffected English reading habit since its coefficientcorrelation is the highest 0,76.
Keywords: Reading habit; reading proficiency; reading attitude